Atypical Mansonella ozzardi Microfilariae from an Endemic Area of Brazilian Amazonia - Ta-Tang, Thuy-Huong (Am J Trop Med Hyg, 2016)
Mansonellosis is endemic in several regions of Africa, the Caribbean, and Latin America. Mansonella ozzardi and Mansonella perstans have been reported in Latin America, including the Amazon region. A morphological and molecular microfilariae study was performed in Pauini (Brazil). Blood samples were collected from 40 individuals, and were analyzed by Giemsa-stained blood film and by two different nested polymerase chain reactions which detect internal transcribed spacer-1 and the major sperm protein gene. By microscopy, 14 of 40 were positive: 11 as M. ozzardi and three as M. perstans–like infections. Both molecular methods detected 19 positive cases as M. ozzardi, including those 14 individuals detected by microscopy, without detectable genetic differences among any of the 19 positive samples. Molecular techniques showed an improvement of mansonellosis diagnosis and may become an effective tool to evaluate the present status of M. ozzardi and M. perstans in Latin America.